2001
DOI: 10.1128/jvi.75.14.6705-6709.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 (IL-12) and IL-18 Are Important in Innate Defense against Genital Herpes Simplex Virus Type 2 Infection in Mice but Are Not Required for the Development of Acquired Gamma Interferon-Mediated Protective Immunity

Abstract: Using a combination of gene-targeted mice and neutralizing antibodies, we showed that interleukin-12 (IL-12) and IL-18 are important in the innate control of genital herpes simplex virus type 2 infection but were not found to be critical, either singly or in combination, for the development of a protective gamma interferonmediated immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 47 publications
(28 reference statements)
4
70
0
Order By: Relevance
“…Particularly noteworthy is the lack of regulation of IFN-␥ production in the lung by either IL-12 or IL-18, indicating other mechanisms of IFN-␥ induction in RSV infection. This finding is consistent with that found in genital herpes simplex type 2 infection (57). Similarly, a recent study also showed that IL-12 and IL-18 are not required for a pronounced Th1 response to RSV infection (58).…”
Section: Discussionsupporting
confidence: 81%
“…Particularly noteworthy is the lack of regulation of IFN-␥ production in the lung by either IL-12 or IL-18, indicating other mechanisms of IFN-␥ induction in RSV infection. This finding is consistent with that found in genital herpes simplex type 2 infection (57). Similarly, a recent study also showed that IL-12 and IL-18 are not required for a pronounced Th1 response to RSV infection (58).…”
Section: Discussionsupporting
confidence: 81%
“…However, IFN-␥ responses in the lymphoid organs appeared to be dominant. We and others have previously documented the critical importance of IFN-␥ response for immune protection against genital herpes infection in mice (23)(24)(25)(26). Furthermore, we could show that mice immunized with gD plus ␣-GalCer had high levels of gD-specific IgG Abs in their sera and vaginal extracts.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, neutralization of IL-12p40 in BALB/c mice was found to significantly diminish the antiviral CTL response to the more virulent A/PR/8 strain of influenza virus (16). On the other hand, although both cytokines were found to be important for control of HSV-2 by innate immunity, neither was needed for generation of adaptive immune effector mechanisms (17). Finally, neither IL-12p40 nor IL-18 were found to be necessary for the control of respiratory syncytial virus infection or IFN-␥ production, although both cytokines contributed to limiting lung inflammation and Th2 responses (18).…”
Section: P Roduction Of the Th1 Cytokine Ifn-␥ By Nk And T Cells Is Cmentioning
confidence: 99%